Feminism, diversity and HRD - Metcalfe, Beverly Dawn; Makarem, Yasmeen (New York, NY : Routledge, 2024)
"Feminism, Diversity and HRD aims to enhance critical understandings of feminism, diversity and HRD theorization and practice in the global political economy. This involves addressing race, class and intersectional approaches to evaluating inequalities in society/organizations. The book will bring together cutting-edge analysis to offer a critical interdisciplinary overview of the feminism, diversity and HRD debates that are only just emerging. Crucially, it will offer new insights on the governance and policy-making dimensions of national HRD, and the gender agendas advocated by global institutions which are influenced by social justice themes. In this respect, the contributions in this volume offer more than just a tried and tested analysis of the political, knowledge and skill gap problems that face organizations and nation states. Rather, they are agenda-setting and forward-looking since they critically consider what the HRD solutions currently on offer are, and how they can be further improved. Thus, the contributions will cover theoretical and policy perspectives not previously covered in a critical text of this kind"--
Keywords: Feminism; Manpower policy; Diversity in the workplace; BUSINESS & ECONOMICS / Human Resources & Personnel Management